The Effects of Therapeutic Play for Reducing Impact Hospitalization Pre and School-Age In Hospital: A Systematic Review - Setiawati, Santun; Wanda, Dessie; Agustini, Nur; Whulanza, Yudan; Keliat, Budi Anna (Poltekkes Kemenkes Palu, 2024)
This systematic review aimed to identify the effectiveness of therapeutic play in reducing the impact of hospitalization on pre and school-aged children. Five databases were searched (ClinicalKey Nursing, Scopus, Sage Journals, ScienceDirect, and PubMed) for articles published between 2019 and 2023. Six RCT studies from Turkey met the inclusion criteria and were assessed for quality using the JBI Critical Appraisal Checklist. The therapeutic play interventions included goldfish therapy, educational animated films, finger puppet play, music and kaleidoscope therapy, cartoon-assisted endoscopy preparation packages, and buzzy, jet lidocaine, bubble-blowing, and aromatherapy. The duration of the interventions varied. The outcomes measured were anxiety, fear, pain, emotional and psychological well-being, and postoperative nausea and vomiting. The results showed that therapeutic play significantly reduced anxiety (50% of studies), fear (100%), and pain (50%) in children undergoing hospitalization or medical procedures. Goldfish therapy also improved emotional and psychological well-being. No significant differences were found in postoperative vomiting and nausea. The most effective interventions were goldfish therapy, educational animated films, and finger puppet play. In conclusion, therapeutic play is a beneficial nursing intervention for reducing the negative impacts of hospitalization on children aged 3-12 years. Recommendations include implementing therapeutic play in pediatric hospital settings and conducting further research to expand the types of therapeutic play available.